2015
DOI: 10.1007/s11357-015-9856-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a physical training program using the Pilates method on flexibility in elderly subjects

Abstract: The adaptations of the human body resulting from the aging process especially loss of flexibility can increase the risk of falls and the risk of developing other health conditions. Exercise training, in particular the Pilates exercise method, has become an important form of physical activity that minimizes the deleterious effects of aging on flexibility. Few studies have evaluated the effect of this training method on body flexibility among elderly. We aimed to evaluate the effects of physical training using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 41 publications
1
16
0
5
Order By: Relevance
“…The results of the studies by Bird 25 , with 15 sessions, and of Donath 33 and Kaesler 34 , with 16 sessions, did not present improvement of muscular strength, whose possible reason is that the little time practiced was not sufficient to promote gains in this variable. On the other hand, Pinheiro et al 35 , with only 12 sessions, observed a significant improvement in paravertebral muscle strength. In spite of the relatively low number of sessions, in this specific case, the positive results are consistent due to the small sample studied.…”
Section: Muscle Strengthmentioning
confidence: 89%
“…The results of the studies by Bird 25 , with 15 sessions, and of Donath 33 and Kaesler 34 , with 16 sessions, did not present improvement of muscular strength, whose possible reason is that the little time practiced was not sufficient to promote gains in this variable. On the other hand, Pinheiro et al 35 , with only 12 sessions, observed a significant improvement in paravertebral muscle strength. In spite of the relatively low number of sessions, in this specific case, the positive results are consistent due to the small sample studied.…”
Section: Muscle Strengthmentioning
confidence: 89%
“…En cuanto al diseño, diez fueron estudios pre-post con un grupo de intervención (Bergamin et al, 2015;Bertoli et al, 2017Bertoli et al, , 2018Bird & Fell, 2014;Choi et al, 2019;Geremia, Iskiewicz, Marschner, Lehnen & Lehnen, 2015;Pata et al, 2014;Pérez et al, 2014;Pinheiro et al, 2014;Ruiz-Montero et al, 2014;Scherf et al, 2019) y seis pre-post con un grupo control y uno experimental de Carvalho et al, 2017;Irez, 2014;Ruiz-Montero & Castillo-Rodriguez, 2018;Sofianidis et al, 2017;Vasconcelos et al, 2016); cuatro ensayos clínicos aleatorizados (de Oliveira, Liposcki et al, 2019;Vieira et al, 2017); quince ensayos controlados aleatorizados (Aibar-Almazán et al, 2019;Aibar-Almazan et al, 2019;Barker et al, 2016;Cruz-Diaz et al, 2015;de Oliveira, de Oliveira & Pires-Oliveira, 2016;de Oliveira et al, 2018;Gabizon et al, 2016;Josephs et al, 2016;Markovic et al, 2015;Mesquita et al, 2015;Roller et al, 2018); dos estudios transversales (Ruiz-Montero et al, 2015) y un estudio piloto (Jurakic et al, 2017) (tabla 1).…”
Section: Resultsunclassified
“…Não há um marcador único geral de flexibilidade corpórea, mais sim são analisados tais fatores por segmentos, nessa lógica, outro estudo, conduzido em poucas sessões de treinamentos 18 , relatou esses acréscimos quanto aos níveis de flexibilidade em determinadas partes do corpo, porém em outras não. Quanto a isso é necessário considerar se os exercícios incluídos no programa, estão apresentados a mesma ênfase muscular a todas as partes analisadas, ademais, se esse curto período da intervenção foi suficiente para causar mudanças na flexibilidade nos diferentes segmentos corporais.…”
Section: Discussionunclassified